High voltage gain DC-DC converter using interleaved switching technique with PWM for current stress - Abd Samat, Mohd Nasri (2019)
This project proposed a high voltage gain DC-DC converter with high boost ratio by using Interleaved switching technique in order to reduce the inductance of inductor required in the proposed converter circuit structure. This project considered Marx generator principle to boost-up the voltage where the boost ratio used is 8.33 with three stages of high voltage gain DC-DC converter. By using the Marx topology to boost-up voltage, the reduction of current stress at the switching devices cause the reduction of conduction loss and switching loss. The efficiency of the proposed converter will be compared by using interleaved switching technique and synchronous switching technique. Principally, the interleaved switching technique able to reduce the current stress on the component. By using interleaved switching technique, the current stress on the components reduces about 35% when using 640 μH and 64% when using 800 μH of output inductance compared to synchronous switching technique When synchronous switching pattern is considered, the output voltage obtain is 375 V and the transient response is 0.02 s. However, by implementing interleaved switching pattern the output voltage obtain is 410 V by considering the practical condition and the transient response improved to 0.01 s. Thus, when the proposed of high voltage gain DC-DC converter is considered with interleaved switching technique, the current stress on the components could be reduced and consequently, the overall losses of the converter can be reduced.